Developing a Program Plan Based on the Program Planning Cycle - John M. Diaz; Cody Gusto; David Diehl (EDIS)
For over a century, Cooperative Extension services within the United States have utilized specific program development plans to create or refine optimal programmatic services for clientele (Franz, Garst, Gagnon, 2015). Though developmental models may vary, planning or refinement in any program features some core developmental principles. This article provides an overview of these fundamental tenets within program planning, how a planning process informs an overarching development plan, and why these components are integral to Extension services. The article outlines how the incorporation of a planning process and the application of targeted, outcome-focused planning principles is paramount in building a program capable of delivering sustainable and desirable outcomes to clients.